2021
DOI: 10.1177/0003134821998664
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Transaminases in Predicting Choledocholithiasis. A Novel Predictive Composite Score Development in a Cohort of 1089 Patients Undergoing Laparoscopic Cholecystectomy

Abstract: Background Optimal use of interventional procedures and diagnostic tests for patients with suspected choledocholithiasis depends on accurate pretest risk estimation. We sought to define sensitivity/specificity of transaminases in identifying choledocholithiasis and to incorporate them into a biochemical marker composite score that could accurately predict choledocholithiasis. Methods All adult patients who underwent laparoscopic cholecystectomy by our Emergency Surgery Service between 2010 and 2018 were review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…28 , in a prospective study performed on 350 patients for the assessment of liver function tests in the diagnosis of CBDSs in patients with cholecystitis, found ALT as an independent predictor of cholelithiasis (OR: 2; P =0.04). More recently, novel predictive scores are being proposed showing AUC of 0.77 and 0.76 for AST and ALT, respectively, in a cohort of 1089 patients 29 . Other descriptive studies have shown AST as the least sensitive parameter altered in ∼50.8% of the cases 30 .…”
Section: Discussionmentioning
confidence: 99%
“…28 , in a prospective study performed on 350 patients for the assessment of liver function tests in the diagnosis of CBDSs in patients with cholecystitis, found ALT as an independent predictor of cholelithiasis (OR: 2; P =0.04). More recently, novel predictive scores are being proposed showing AUC of 0.77 and 0.76 for AST and ALT, respectively, in a cohort of 1089 patients 29 . Other descriptive studies have shown AST as the least sensitive parameter altered in ∼50.8% of the cases 30 .…”
Section: Discussionmentioning
confidence: 99%